Do global ao doméstico: regimes de proteção às indicações geográficas, produção tradicional e desenvolvimento - Lucas Costa dos Anjos (2016)
This dissertation seeks to better understand the relationship between geographical indications and regional economic development, within the context of intellectual property regulations, whether under the aegis of Municipal Law, whether under the aegis of International Law. Specifically, it intends to analyze how is this category of intellectual property rights able to promote and to value physical and human attributes of a region, to prevent unauthorized use and to allow for financial return, added value, consumers market loyalty, culture and traditions upkeep, market differentiation and furtherance of local tourism. It assumes that unauthorized use of geographical indications can enable the failure of traditional producers and to generate several losses, such as the disorganization of familycentered productions. This subject is particularly relevant in the context of emerging markets, where products recognized by its tradition and local productive culture carry characteristics hard to be appropriated by the industry nowadays. In addition to national instruments that protect intellectual property, such as the Federal Constitution of Brazil (article 5, XXIX) and Law n. 9,279, of 1996, this dissertation will analyze contemporary initiatives to broaden the scope of international protection beyond the TRIPS Agreement and other international treaties in force, especially with regard to the Doha Round of negotiations (also known as the Development Round), within the World Trade Organization and the Development Agenda for the World Intellectual Property Organization. Among the subjects being negotiated, is the organization of a multilateral registry and notification system for the geographical indications of wine and spirits. Members that stand for a broader protection believe that a comprehensive regulation system for geographical indications would reduce unfair use, facilitate international trade and promote development.